Importance of basal boundary conditions in transient simulations : case study of a surging marine-terminating glacier on Austfonna, Svalbard - Gong, Yongmei; Zwinger, Thomas; Cornford, Stephen; Gladstone, Rupert; Schäfer, Martina; Moore, John (Journal of Glaciology, 2017)
We assess the importance of basal boundary conditions for transient simulations of Basin 3, Austfonna ice cap between January 1995 and December 2011 and for the surge starting in 2012 by carrying out simulations with the full-Stokes model Elmer/Ice and the vertically-integrated model BISICLES. Time-varying surface mass-balance data from the regional climate model HIRHAM5 are downscaled according to elevation. Basal friction coefficient is varied through time by interpolating between two data-constrained inversions of surface velocity fields, from 1995 and 2011. Evolution of the basal boundary condition appears to be much more important for mass discharge and the dynamic response of the fast flowing unit in Basin 3 than either model choice or the downscaling method for the surface mass balance. In addition, temporally linear extrapolation of the evolution of basal friction coefficient beyond the 2011 distribution could not reproduce the expansion of the acceleration observed in southern Basin 3 between January 2012 and June 2013. This implies that changes in basal friction patterns, and in turn basal processes that are not currently represented in either model, are among the most important factors for the 2012 acceleration. Peer reviewed